The COVID-19 Pandemic and the Incidence of the Non-COVID-19 Pneumonia in Adults - Huang, Chienhsiu (Frontiers in Medicine, 2021)
Introduction: The COVID-19 lockdown strategies were associated with a significant decrease in common respiratory viral diseases and decreased the need for hospitalisation among children in the COVID-19 outbreak. However, the trend of non-COVID-19 pneumonia in adult people remains uncertain. Our aimed to assess the impact of the COVID-19 pandemic on the incidence of non-COVID-19 pneumonia in adult people and understand whether the substantial decrease in pneumonia cases is the same as the decline in the incidence of respiratory viral disease activity. Methods: We conducted a retrospective analysis of adult patients presenting with pneumonia from January 2019 to December 2020. Details on all pneumonia patient demographics, hospital course details, prior admission history within 3 months, respiratory culture, and antibiotics sensitivity test were also obtained. Results: The number of adult patients with community-acquired pneumonia in 2020 was lower than that in 2019, decreasing by 74 patients in 2020. The decreasing number of patients with community-acquired pneumonia between 2019 and 2020 was from -13.9% in the 2020 January to March to –39.7% in 2020 October to December. The decreasing number of community-acquired pneumonia patients between 2019 and 2020 was from −14.8% in the youngest cohort to −28.7% in those aged ≥85 years. The number of reduced community-acquired pneumonia patients is greater in late seasons and older age, respectively. The number of adult patients with hospital-acquired pneumonia in 2020 was lower than that in 2019, which decreased by 23 patients in 2020. The decreasing number of patients with hospital-acquired pneumonia between 2019 and 2020 was from −20.0% in January to March to −52.4% in October to December 2020. The decreasing number of patients with hospital-acquired pneumonia between 2019 and 2020 was from 0% in the youngest cohort to −45.6% in those aged ≥85 years. The number of reduced hospital-acquired pneumonia patients is greater in late seasons and older age, respectively. Conclusions: Interventions applied to control the COVID-19 pandemic were effective not only in substantial changes in the seasonal influenza activity but also in decreasing adult pneumonia cases.